2016
DOI: 10.1111/bjd.14690
|View full text |Cite
|
Sign up to set email alerts
|

Possible paradoxical occurrence of inflammatory arthritis in patients with psoriasis treated with biologics: findings in the Biobadaderm cohort

Abstract: 1516 0 0 (0-2Á4) a CI, confidence interval. a Calculated using Poisson distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…All stages of syphilis require treatment. 3 We present a rare case of tertiary syphilis in our clinical practice.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…All stages of syphilis require treatment. 3 We present a rare case of tertiary syphilis in our clinical practice.…”
mentioning
confidence: 93%
“…However, a high-dose tofacitinib regimen may increase the risks of systemic AEs. 3 Low-dose (5 mg daily) tofacitinib has shown efficacy for severe alopecia areata, which shares a mechanistic link with vitiligo. 4 We previously reported that low-dose tofacitinib with narrowband ultraviolet B (NB-UVB) therapy for 16 weeks is insufficient to treat refractory vitiligo, and only one out of four patients showed marked repigmentation.…”
mentioning
confidence: 99%
“…The incidence of PsA in our study shows that the use of biologic drugs does not seem to completely protect against the possibility of a future development of PsA; hence, dermatologist attention and screening for PsA must continue also in patients under biologics. Conversely, it should be also underlined that biologic treatment strongly reduced the incidence of PsA, which can reach up to 20% of patients with psoriasis [61]. In fact, a recent 8-year retrospective non-randomized study [50] tried to assess the incidence of PsA in patients with moderate-to-severe plaque psoriasis comparing subjects under biologic treatment prescribed for at least 5 years (infliximab, etanercept, adalimumab, ustekinumab, secukinumab) with patients treated with narrow-band ultraviolet light B (nbUVB).…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis with HIV infection may have a more severe course with sudden exacerbations and may be refractory to treatment . Paradoxical onset of psoriasis and arthritis is also demonstrated in patients treated with biologicals . Anti‐TNF‐ α antibodies frequently induce increased levels of KL‐6, which is a serum marker for interstitial pneumonia .…”
Section: Autoimmunity In Psoriasismentioning
confidence: 99%
“…[114][115][116][117][118] Paradoxical onset of psoriasis and arthritis is also demonstrated in patients treated with biologicals. 119,120 Anti-TNF-a antibodies frequently induce increased levels of KL-6, which is a serum marker for interstitial pneumonia. 121 In addition, the onset and exacerbation of psoriasis have been reported in melanoma patients treated with the anti-programmed cell death protein 1 antibody nivolumab.…”
Section: Autoimmunity In Psoriasismentioning
confidence: 99%